Revitalizing Classical Arabic Literature as a Basis for Character Education: A Literary Analysis of Imad al-Isfahani’s Poetry - Muhammad Hagdhak Al-Ghafiqi (Yayasan Cerdas Pedia Indonesia, 2026)
This research addresses moral degradation in Indonesia's 2025 educational landscape by revitalizing classical Arabic literature. It specifically analyzes Imad al-Isfahani’s poem